Determinants of precancerous cervical lesion among HIV infected women on ART in Woldia comprehensive specialized hospital NorthEast Ethiopia - Tazeb Melkie Dessie; Abebe Tarekegn Kassaw; Gedefaw Diress Alen (BMC, 2023)
Abstract Background Precancerous cervical lesion is a priority public health problem that jeopardizes the life of enormous women. previous studies in Ethiopia were more focused on knowledge, attitude, and practices of Cervical cancer screening. studies on the risk factors of pre-cancerous cervical lesions among the risk population (HIV infected) relative to the general population were limited. This study aimed to identify the determinants of precancerous cervical lesions among HIV Infected Women in Woldia Comprehensive Specialized Hospital in Northeast Ethiopia, 2022. Methods Hospital-based unmatched case-control study was conducted in Woldia Comprehensive Specialized Hospital among HIV-infected women from June to August 2022. Data were collected from 104 cases and 208 controls using an interviewer-administered questionnaire and clinical data from the patient chart using Electronic Medical Record _ Anti-Retroviral Therapy Smart care database checklist. The binary logistic regression model was used to identify the determinants of the precancerous cervical lesion. An odds ratio with a 95% Confidence interval was used to measure the association and p-value < 0.05 were considered significant. Results Women who have two or more lifetime sexual partners (AOR = 3.21,95% CI: 1.71-6.04), history of sexually transmitted infection (AOR = 4.97, 95% CI: 2.78-8.78), early age at first sexual intercourse (< 18 years) (AOR = 4.35,95% CI: 2.48-7.67) and baseline CD4 count < 200 cells/mm3 (AOR = 1.89, 95% CI: 1-3.57) had a higher odd of developing a precancerous cervical lesion. Conclusion This study confirms that having a history of sexually transmitted infection, two or more lifetime sexual Partners, the initiation of sexual intercourse before the age of 18 years, and Baseline CD4 count < 200 cells/mm3 were determinants for precancerous cervical lesions. So it should be focused on prevention through early detection and treatment of sexually transmitted infections.